Preparation method of acrylic resin with high adhesive force

Through improved preparation steps, combined with the addition of nanocellulose whiskers and nanosilicon dioxide, the adhesion and mechanical properties of the acrylic resin are improved, and the problems of insufficient viscosity and poor corrosion resistance in the prior art are solved, thus achieving further development High photolithography accuracy and stability.

CN119264335AInactive Publication Date: 2025-01-07LINKOP (JILIN) NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411505114.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The viscosity of the epoxy acrylic resin prepared in the prior art is insufficient, and its corrosion resistance and mechanical properties need to be improved.

Method used

Preparation steps: add fatty alcohol polyoxyethylene ether and sodium dodecyl sulfate to distilled water, add initiator dropwise after heating, add shell monomer mixture and react; add dibasin to isophorone diisocyanate dropwise Dibutyltin and hydroxyethyl methacrylate were added, γ-mercaptopropyltriethoxysilane was added; modified nanocellulose whiskers and nanosilia were added to the mixed solution to form a high adhesion acrylic resin.

Benefits of technology

It improves the adhesion, mechanical properties and corrosion resistance of the resin, reduces the curing shrinkage rate, and enhances the density and lithography accuracy of the adhesive film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264335A_ABST
    Figure CN119264335A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of acrylic resin with high adhesive force, and relates to the technical field of acrylic resin preparation, and the preparation method comprises the following preparation steps: step 1, sequentially adding fatty alcohol-polyoxyethylene ether and lauryl sodium sulfate into distilled water, after the fatty alcohol-polyoxyethylene ether and the lauryl sodium sulfate are completely dissolved, adding a core monomer mixed solution, heating to 45-50 DEG C, and reacting for 1-2 hours; the preparation method comprises the following steps: adding a shell monomer into a reaction kettle, reacting for 30-35 minutes, dropwise adding half of an initiator, heating to 75-80 DEG C after dropwise adding, reacting for 2-2.2 hours, adding the rest of a mixed solution of the initiator and the shell monomer, reacting for 1.9-2 hours at the temperature of 80-85 DEG C, and cooling to room temperature to obtain a mixed solution A; according to the preparation method of the acrylic resin with the high adhesive force, nano silicon dioxide is modified, so that the dispersity and compatibility of nano particles are effectively improved, and after the nano silicon dioxide is added into the acrylic resin, the curing shrinkage rate of the acrylic resin can be reduced, so that the photoetching precision of photoresist is improved; and more accurate micro-nano processing is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic resin preparation, in particular to a method for preparing acrylic resin with high adhesion. Background Art

[0002] Photoresist, also known as photoresist, refers to a thin film material whose solubility changes when exposed to ultraviolet light, electron beam, ion beam, X-ray, etc. It is a light-sensitive mixed liquid composed of three main components: photosensitive resin, sensitizer and solvent.

[0003] Chinese patent publication number CN115926111A discloses a composition of epoxy acrylic resin for LDI photoresist, comprising the following raw materials: 10-30 parts of epoxy resin, 20-50 parts of acrylic acid, 8-15 parts of polyol, 5-10 parts of catalyst, 3-8 parts of polymerization inhibitor, and 3-6 parts of initiator. The composition comprises: firstly physically modifying the epoxy resin with a certain amount of polyol, then adding a certain amount of acrylic acid to photoactively modify the epoxy resin, then adding the catalyst and polymerization inhibitor and stirring evenly, finally dropping the initiator, and discharging the product without cooling. The polyol is one of pentaerythritol, ethylene glycol (EG), 1,2-propylene glycol (1,2-PG), 1,4-butanediol (BDO), 1,6-hexanediol (HD), neopentyl glycol (NPG), diethylene glycol (EG), dipropylene glycol (PG), and trimethylolpropane (TMP). The present invention facilitates control of the viscosity of the composition during preparation, and by testing each component at varying weights, provides a concrete indication of the cure rate. However, the viscosity of the resin prepared using the prior art needs to be further increased, and the corrosion resistance and mechanical properties of the resin also need to be improved. To address these issues, the present invention provides a method for preparing a high-adhesion acrylic resin to address these issues. Summary of the Invention

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high-adhesion acrylic resin, which solves the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a high-adhesion acrylic resin, comprising the following preparation steps:

[0006] Step 1: Add fatty alcohol polyoxyethylene ether and sodium lauryl sulfate to distilled water in sequence. After they are completely dissolved, add the core monomer mixture, heat to 45-50°C, react for 30-35 minutes, and then add half of the initiator dropwise. After the addition is complete, heat to 75-80°C and react for 2-2.2 hours. Then, add the remaining initiator and shell monomer mixture, react at 80-85°C for 1.9-2 hours, and then cool to room temperature to obtain a mixed solution A.

[0007] Step 2: After pouring isophorone diisocyanate into the blender, nitrogen was introduced for 30 to 40 minutes, dibutyltin dilaurate was added dropwise, and then p-methoxyphenol was added and stirred evenly. The temperature was then raised to 72 to 75°C, and hydroxyethyl methacrylate was slowly added dropwise. After reacting for 3 to 3.2 hours, the temperature was lowered to 50 to 55°C, and γ-mercaptopropyltriethoxysilane was added dropwise. After reacting at a constant temperature of 70 to 72°C for 2.8 to 3 hours, the mixture was cooled to room temperature to obtain a mixed solution B.

[0008] Step 3: Pour 5wt% to 10wt% of mixed solution B into 75wt% to 90wt% of mixed solution A, stir and mix, and then add 5wt% to 8wt% of modified nanocellulose whiskers and 4wt% to 9wt% of modified nanosilica to obtain a high-adhesion acrylic resin.

[0009] Preferably, in step 1, the weight proportions of the components are: 30-32 parts of distilled water, 0.7-0.75 parts of fatty alcohol polyoxyethylene ether, 0.5-0.6 parts of sodium lauryl sulfate, 24.6-25.2 parts of core monomer mixture, 0.4-0.5 parts of initiator, and 29.9-31.1 parts of shell monomer mixture.

[0010] Preferably, in step 2, the weight proportions of the components are: 6.4 to 6.7 parts of isophorone diisocyanate, 0.2 to 0.8 parts of dibutyltin dilaurate, 0.2 to 0.3 parts of p-methoxyphenol, 3.2 to 3.5 parts of hydroxyethyl methacrylate, and 6.4 to 6.7 parts of γ-mercaptopropyltriethoxysilane.

[0011] Preferably, the core monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate and isooctyl acrylate, and the mass ratio thereof is 7.6:(7.3-7.4):(9.7-10.2).

[0012] Preferably, the shell monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate, isooctyl acrylate, dodecafluoroheptyl methacrylate and trimethylolpropane triacrylate, and the mass ratio thereof is 10:(7-7.5):(7.3-7.6):(3.8-4):(1.8-2).

[0013] Preferably, the initiator is azobisisobutyronitrile, and the preparation method of the high-adhesion acrylic resin further comprises purifying the initiator, and the specific processing method is:

[0014] (1) Heat 42-48 mL of anhydrous ethanol in a water bath to 70-75°C;

[0015] (2) Add 1.2-1.6 g of azobisisobutyronitrile, stir until completely dissolved, and filter;

[0016] (3) The filtrate is cooled at a low temperature of 2 to 4°C for 22 to 24 hours, then washed with methanol for 3 to 5 times, and finally dried.

[0017] Preferably, the preparation method of the modified nano-silica is:

[0018] Ⅰ. In a water bath at 40-45°C, mix 20-26 mL of anhydrous ethanol and aqueous ammonia at a volume ratio of 1:1 and stir for 12-15 minutes.

[0019] II. Add 10-16 mL of ethyl orthosilicate dropwise and allow to react for 3.8-4 hours after the addition is complete.

[0020] III. Heat the water bath to 50-55°C, add 0.2-0.4g of modifier, and keep warm for 22-24h;

[0021] IV. After centrifugation and washing with ethanol for 4 to 5 times, the mixture is dried in a vacuum drying oven at 55 to 60° C. to obtain modified nano-silica.

[0022] Preferably, the preparation method of the modifier is as follows: a mixture of 3 mL of water and 7 mL of ethanol is added to 0.08 to 0.1 g of γ-methacryloxypropyltrimethoxysilane, and ultrasonic dispersion is performed for 10 to 15 minutes.

[0023] Preferably, the preparation method of the modified nanocellulose whiskers is:

[0024] 1) Pour 340 mL of 64% sulfuric acid aqueous solution into 18-20 g of absorbent cotton and stir in a 45-50°C water bath for 15-20 min;

[0025] 2) adding 150-180 mL of deionized water, washing by centrifugation, and then replacing the solvent with acetone and N,N-dimethylformamide in sequence until the solution concentration reaches 10 wt%;

[0026] 3) Raise the temperature to 80-85°C and add 1.6-2 g of dimethylaminopyridine dropwise while stirring. React for 50-60 minutes.

[0027] 4) adding 0.8-1.3 g of dodecenylsuccinic anhydride dropwise, and continuing stirring for 3.6-4 h after the addition is complete, then cooling to room temperature, and washing 3-5 times to obtain modified nanocellulose whiskers.

[0028] Beneficial effects

[0029] The present invention provides a method for preparing a high-adhesion acrylic resin. Compared with the prior art, the method has the following advantages:

[0030] (1) The preparation method of the high-adhesion acrylic resin is to modify the nano-silica to effectively improve the dispersibility and compatibility of the nanoparticles, so that after adding the nano-silica to the acrylic resin, the curing shrinkage of the acrylic resin can be reduced, thereby improving the photolithography accuracy of the photoresist and achieving more precise micro-nano processing.

[0031] (2) The method for preparing the high-adhesion acrylic resin ensures the quality and purity of azobisisobutyronitrile by purifying it, thereby ensuring the stability and controllability of the acrylic resin preparation process. The role of azobisisobutyronitrile in the acrylic resin preparation process is to initiate the polymerization reaction of propylene monomers through the free radicals generated by its decomposition, and the purification treatment is to ensure the stability of the polymerization reaction and the quality of the final product.

[0032] (3) The preparation method of the high-adhesion acrylic resin increases the high-energy Si-O bonds and relatively stable isocyanate hexacyclic rings in the polymer system by synergistically adding the core monomer mixture and the shell monomer mixture, resulting in a significant increase in the energy required for the decomposition system; on the other hand, the siloxane is hydrolyzed and condensed to form a Si-O-Si cross-linked network structure, which not only enhances the structural stability but also significantly improves the density of the film surface layer, increases the cross-linking density of the acrylic resin dispersion, and forms a closed network structure, thereby improving the mechanical properties, viscosity and corrosion resistance of the resin.

[0033] (4) The preparation method of the high-adhesion acrylic resin significantly improves the dispersibility and compatibility of the nanocellulose whiskers in the resin by modifying the nanocellulose whiskers, effectively avoids the agglomeration of the nanocellulose whiskers, ensures their uniform distribution in the resin, and thus improves the bonding performance and mechanical properties of the resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a comparison chart of the mechanical properties test provided by the present invention. DETAILED DESCRIPTION

[0035] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0036] In the present technical solution, the preparation method of the modifier is as follows: a mixture of 3 mL of water and 7 mL of ethanol is added to 0.1 g of γ-methacryloxypropyltrimethoxysilane, and ultrasonic dispersion is performed for 15 minutes.

[0037] Example 1

[0038] A method for preparing a high-adhesion acrylic resin comprises the following steps:

[0039] Step 1: Purification of azobisisobutyronitrile: Heat 42 mL of anhydrous ethanol in a water bath to 70°C, then add 1.2 g of azobisisobutyronitrile, stir until completely dissolved, and filter. Cool the filtrate at 2°C for 22 hours, then wash with methanol three times, and finally dry.

[0040] Step 2: To 30 g of distilled water, 0.7 g of fatty alcohol polyoxyethylene ether and 0.5 g of sodium lauryl sulfate were added in sequence. After complete dissolution, 24.6 g of the core monomer mixture was added, the temperature was raised to 45 ° C, and the reaction was continued for 30 minutes. After that, 0.1 g of azobisisobutyronitrile was added dropwise. After the addition was completed, the temperature was raised to 75 ° C and the reaction was continued for 2 hours. Then, 0.1 g of azobisisobutyronitrile and 29.9 g of the shell monomer mixture were added, and the mixture was reacted at 80 ° C for 1.9 hours, and then cooled to room temperature to obtain a mixed solution A;

[0041] The core monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate and isooctyl acrylate, and the mass ratio thereof is 7.6:7.3:9.7; the shell monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate, isooctyl acrylate, dodecafluoroheptyl methacrylate and trimethylolpropane triacrylate, and the mass ratio thereof is 10:7:7.3:3.8:1.8;

[0042] Step 3: After pouring 6.4 g of isophorone diisocyanate into the blender, nitrogen was introduced for 30 min, 0.2 g of dibutyltin dilaurate was added dropwise, and 0.2 g of p-methoxyphenol was added and stirred evenly. The mixture was then heated to 72 ° C. 3.2 g of hydroxyethyl methacrylate was slowly added dropwise. After reacting for 3 h, the mixture was cooled to 50 ° C. 6.4 g of γ-mercaptopropyltriethoxysilane was added dropwise. After reacting at a constant temperature of 70 ° C for 2.8 h, the mixture was cooled to room temperature to obtain a mixed solution B.

[0043] Step 4: Pour 5 wt% of mixed solution B into 86 wt% of mixed solution A, stir and mix, and then add 5 wt% of modified nanocellulose whiskers and 4 wt% of modified nanosilica to obtain a high-adhesion acrylic resin;

[0044] The preparation method of modified nano-silica is as follows: 20 mL of anhydrous ethanol and ammonia water in a volume ratio of 1:1 were mixed and stirred for 12 minutes in a water bath at 40°C; 10 mL of ethyl orthosilicate was added dropwise, and after the addition was complete, the mixture was reacted for 3.8 hours; the water bath was heated to 50°C, 0.2 g of the modifier was added, and the mixture was kept warm for 22 hours; after centrifugation and washing with ethanol four times, the mixture was dried in a vacuum drying oven at 55°C to obtain modified nano-silica;

[0045] Preparation method of modified nanocellulose whiskers: pour 340 mL of 64% sulfuric acid aqueous solution into 18 g of absorbent cotton, and stir in a 45°C water bath for 15 minutes; then add 150 mL of deionized water, centrifuge and wash, and then use acetone and N,N-dimethylformamide to replace the solvent in sequence until the solution concentration reaches 10 wt%; heat to 80°C, and add 1.6 g of dimethylaminopyridine dropwise while stirring, and react for 50 minutes; add 0.8 g of dodecenylsuccinic anhydride dropwise, and after the addition is complete, continue stirring for 3.6 hours, then cool to room temperature, and wash three times.

[0046] Example 2

[0047] A method for preparing a high-adhesion acrylic resin comprises the following steps:

[0048] Step 1: Purification of azobisisobutyronitrile: Heat 45 mL of anhydrous ethanol in a water bath to 75°C, then add 1.4 g of azobisisobutyronitrile, stir until completely dissolved, and filter. Cool the filtrate at 3°C ​​for 23 hours, then wash with methanol 4 times, and finally dry.

[0049] Step 2: To 31 g of distilled water, 0.75 g of fatty alcohol polyoxyethylene ether and 0.5 g of sodium lauryl sulfate were added in sequence. After complete dissolution, 25 g of the core monomer mixture was added, the temperature was raised to 50 ° C, and the reaction was carried out for 30 minutes. After that, 0.2 g of azobisisobutyronitrile was added dropwise. After the addition was completed, the temperature was raised to 80 ° C and the reaction was carried out for 22 hours. Then, 0.2 g of azobisisobutyronitrile and 30 g of the shell monomer mixture were added, and the mixture was reacted at 85 ° C for 2 hours, and then cooled to room temperature to obtain a mixed solution A;

[0050] The core monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate and isooctyl acrylate, and the mass ratio thereof is 7.6:7.4:10; the shell monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate, isooctyl acrylate, dodecafluoroheptyl methacrylate and trimethylolpropane triacrylate, and the mass ratio thereof is 10:7.3:7.4:3.9:1.9;

[0051] Step 3: After pouring 6.5 g of isophorone diisocyanate into the blender, nitrogen was introduced for 35 min, 0.5 g of dibutyltin dilaurate was added dropwise, and 0.3 g of p-methoxyphenol was added and stirred evenly. The mixture was then heated to 73 ° C. 3.4 g of hydroxyethyl methacrylate was slowly added dropwise. After reacting for 3.1 h, the mixture was cooled to 55 ° C. 6.5 g of γ-mercaptopropyltriethoxysilane was added dropwise. After reacting at a constant temperature of 72 ° C for 2.9 h, the mixture was cooled to room temperature to obtain a mixed solution B.

[0052] Step 4: Pour 8 wt% of mixed solution B into 80 wt% of mixed solution A, stir and mix, and then add 6 wt% of modified nanocellulose whiskers and 6 wt% of modified nanosilica to obtain a high-adhesion acrylic resin;

[0053] The preparation method of modified nano-silica is as follows: 23 mL of anhydrous ethanol and ammonia water in a volume ratio of 1:1 were mixed and stirred for 13 minutes in a water bath at 45°C; 13 mL of ethyl orthosilicate was added dropwise, and after the addition was complete, the mixture was reacted for 3.9 hours; the water bath was heated to 55°C, 0.3 g of the modifier was added, and the mixture was kept warm for 23 hours; after centrifugation and washing with ethanol five times, the mixture was dried in a vacuum drying oven at 55°C to obtain modified nano-silica;

[0054] The preparation method of modified nanocellulose whiskers is as follows: 340 mL of a 64% sulfuric acid aqueous solution is poured into 19 g of absorbent cotton and stirred in a 50°C water bath for 18 minutes; 165 mL of deionized water is added, and after centrifugal washing, acetone and N,N-dimethylformamide are used in sequence for solvent replacement until the solution concentration reaches 10 wt%; the temperature is raised to 80°C, and 1.8 g of dimethylaminopyridine is added dropwise while stirring, and the reaction is carried out for 55 minutes; 1 g of dodecenylsuccinic anhydride is added dropwise, and after the addition is completed, stirring is continued for 3.8 hours, and then the mixture is cooled to room temperature and washed four times.

[0055] Example 3

[0056] A method for preparing a high-adhesion acrylic resin comprises the following steps:

[0057] Step 1: Purification of azobisisobutyronitrile: Heat 48 mL of anhydrous ethanol in a water bath to 75°C, then add 1.6 g of azobisisobutyronitrile, stir until completely dissolved, and filter. Cool the filtrate at 4°C for 24 hours, then wash with methanol 5 times, and finally dry.

[0058] Step 2: To 32 g of distilled water, 0.75 g of fatty alcohol polyoxyethylene ether and 0.6 g of sodium lauryl sulfate were added in sequence. After complete dissolution, 25.2 g of the core monomer mixture was added, the temperature was raised to 50 ° C, and the reaction was continued for 35 minutes. After that, 0.25 g of azobisisobutyronitrile was added dropwise. After the addition was completed, the temperature was raised to 80 ° C and the reaction was continued for 2.2 hours. Then, 0.25 g of azobisisobutyronitrile and 31.1 g of the shell monomer mixture were added. After the reaction was continued at 85 ° C for 2 hours, the mixture was cooled to room temperature to obtain a mixed solution A.

[0059] The core monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate and isooctyl acrylate, and the mass ratio thereof is 7.6:7.4:10.2; the shell monomer mixture is a mixed solution of methyl methacrylate, butyl acrylate, isooctyl acrylate, dodecafluoroheptyl methacrylate and trimethylolpropane triacrylate, and the mass ratio thereof is 10:7.5:7.6:4:2;

[0060] Step 3: After pouring 6.7 g of isophorone diisocyanate into the blender, nitrogen was introduced for 40 min, 0.8 g of dibutyltin dilaurate was added dropwise, and 0.3 g of p-methoxyphenol was added and stirred evenly. The mixture was then heated to 75 ° C. and 3.5 g of hydroxyethyl methacrylate was slowly added dropwise. After reacting for 3.2 h, the mixture was cooled to 55 ° C. and 6.7 g of γ-mercaptopropyltriethoxysilane was added dropwise. After reacting at a constant temperature of 72 ° C for 3 h, the mixture was cooled to room temperature to obtain a mixed solution B.

[0061] Step 4: Pour 10 wt% of mixed solution B into 76 wt% of mixed solution A, stir and mix, and then add 5 wt% of modified nanocellulose whiskers and 9 wt% of modified nanosilica to obtain a high-adhesion acrylic resin;

[0062] The preparation method of modified nano-silica is as follows: 26 mL of anhydrous ethanol and ammonia water in a volume ratio of 1:1 were mixed and stirred for 15 minutes in a water bath at 45°C; 16 mL of ethyl orthosilicate was added dropwise, and after the addition was complete, the mixture was reacted for 4 hours; the water bath was heated to 55°C, 0.4 g of the modifier was added, and the mixture was kept warm for 24 hours; after centrifugation and washing with ethanol five times, the mixture was dried in a vacuum drying oven at 60°C to obtain modified nano-silica;

[0063] The preparation method of modified nanocellulose whiskers is as follows: 340 mL of a 64% sulfuric acid aqueous solution is poured into 20 g of absorbent cotton and stirred in a 50°C water bath for 20 minutes; 180 mL of deionized water is added, and after centrifugal washing, acetone and N,N-dimethylformamide are used in sequence for solvent replacement until the solution concentration reaches 10 wt%; the temperature is raised to 85°C, and 2 g of dimethylaminopyridine is added dropwise while stirring, and the reaction is carried out for 60 minutes; 1.3 g of dodecenylsuccinic anhydride is added dropwise, and after the addition is completed, stirring is continued for 4 hours, and then the mixture is cooled to room temperature and washed 5 times.

[0064] Comparative Example 1

[0065] Compared with Example 1, the difference is that the purification step of the initiator azobisisobutyronitrile is deleted.

[0066] Comparative Example 2

[0067] Compared with Example 1, the difference is that the modified nano-silica is replaced by nano-silica.

[0068] Comparative Example 3

[0069] Compared with Example 1, the difference is that the modified nanocellulose whiskers are replaced by nanocellulose whiskers.

[0070] Comparative Example 4

[0071] Compared with Example 1, the difference is that the core monomer mixed solution and the shell monomer mixed solution are not added.

[0072] Viscosity test: NDJ-7 rotary viscometer was used to measure the viscosity at room temperature (20°C); the results are shown in Table 1.

[0073] Use 400-grit sandpaper to sand O235 carbon steel, use ethanol to remove iron filings, use acetone solution to degrease, blow dry with cold air, and after the surface is dry, use an adjustable applicator to coat the Q235 carbon steel specimen. Apply the cured resin evenly to the surface of the specimen to a thickness of 60μm. Place the specimen at room temperature for 48 hours. After it is fully cured, perform the following performance tests:

[0074] Corrosion resistance test: The samples were placed in 1 mol / L HSO4 solution and NaOH solution respectively. After 1200 hours, the surface condition of the samples was observed (for bubbles, rust spots, shedding, etc.); the results are shown in Table 1.

[0075] Salt spray resistance test: In a salt spray test chamber, the test temperature was controlled at 35°C and the concentration of NaCl solution was 3.5%. The results are shown in Table 1.

[0076] Curing shrinkage test: Test in accordance with GB / T15223-2008.

[0077] Table 1

[0078] Viscosity value / MPa·s Salt spray resistance / h Surface state Curing shrinkage / % Example 1 980 >504 No change 0.23% Example 2 970 >504 No change 0.25% Example 3 965 >504 No change 0.26% Comparative Example 1 901 479 Blistering + rust spots 2.8% Comparative Example 2 892 472 Rust spots appear 4.1% Comparative Example 3 886 463 Blistering + rust spots 3.4% Comparative Example 4 881 458 Blistering + rust spots 4.1%

[0079] Mechanical properties test: Use a general electric testing machine to measure the tensile strength and elongation at break of the sample at a speed of 100mm / min at (25+1)℃. The sample size is 4mm×25mm and is in the shape of a dumbbell. Each sample is tested 5 times and the average value is calculated. The results are as follows: Figure 1 shown.

[0080] At the same time, the contents not described in detail in this specification belong to the existing technologies well known to those skilled in the art.

[0081] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0082] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the invention, and the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-adhesive acrylic resin, characterized in that: The method comprises the following preparation steps: Step 1: Add fatty alcohol polyoxyethylene ether and sodium dodecyl sulfate to distilled water in sequence, add the core monomer mixture after they are completely dissolved, heat to 45-50°C, react for 30-35 minutes, then drop half of the initiator, heat to 75-80°C after the addition is complete, react for 2-2.2 hours, then add the remaining initiator and shell monomer mixture, react at 80-85°C for 1.9-2 hours, and then cool to room temperature to obtain a mixed solution A; Step 2: After pouring isophorone diisocyanate into the stirrer, nitrogen is introduced for 30 to 40 minutes, dibutyltin dilaurate is added dropwise, and then p-methoxyphenol is added, stirred evenly, and then the temperature is raised to 72 to 75°C, hydroxyethyl methacrylate is slowly added dropwise, and after reacting for 3 to 3.2 hours, the temperature is lowered to 50 to 55°C, γ-mercaptopropyltriethoxysilane is added dropwise, and the mixture is reacted at a constant temperature of 70 to 72°C for 2.8 to 3 hours, and then cooled to room temperature to obtain a mixed solution B; Step 3: Pour 5wt% to 10wt% of the mixed solution B into 75wt% to 90wt% of the mixed solution A, stir and mix, and then add 5wt% to 8wt% of the modified nanocellulose whiskers and 4wt% to 9wt% of the modified nanosilica to obtain a high adhesion acrylic resin.

2. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: In the step 1, the weight proportions of the components are: 30-32 parts of distilled water, 0.7-0.75 parts of fatty alcohol polyoxyethylene ether, 0.5-0.6 parts of sodium lauryl sulfate, 24.6-25.2 parts of core monomer mixture, 0.4-0.5 parts of initiator, and 29.9-31.1 parts of shell monomer mixture.

3. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: In the step 2, the weight proportions of the components are: 6.4-6.7 parts of isophorone diisocyanate, 0.2-0.8 parts of dibutyltin dilaurate, 0.2-0.3 parts of p-methoxyphenol, 3.2-3.5 parts of hydroxyethyl methacrylate, and 6.4-6.7 parts of γ-mercaptopropyltriethoxysilane.

4. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: The core monomer mixed solution is a mixed solution of methyl methacrylate, butyl acrylate and isooctyl acrylate, and the mass ratio thereof is 7.6:(7.3-7.4):(9.7-10.2).

5. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: The shell monomer mixed liquid is a mixed solution of methyl methacrylate, butyl acrylate, isooctyl acrylate, dodecafluoroheptyl methacrylate and trimethylolpropane triacrylate, and the mass ratio thereof is 10:(7-7.5):(7.3-7.6):(3.8-4):(1.8-2).

6. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: The initiator is azobisisobutyronitrile. The preparation method of the high-adhesion acrylic resin further includes purifying the initiator. The specific processing method is: (1) Heat 42-48 mL of anhydrous ethanol in a water bath to 70-75°C; (2) Add 1.2-1.6 g of azobisisobutyronitrile, stir until completely dissolved, and then filter; (3) The filtrate is cooled at a low temperature of 2 to 4°C for 22 to 24 hours, then washed with methanol for 3 to 5 times, and finally dried.

7. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is: Ⅰ. In a water bath at 40-45℃, mix 20-26mL of anhydrous ethanol and ammonia water in a volume ratio of 1:1 and stir for 12-15min. Ⅱ. Add 10-16 mL of ethyl orthosilicate dropwise, and react for 3.8-4 hours after the addition is complete; III. Heat the water bath to 50-55°C, add 0.2-0.4g of modifier, and keep the reaction warm for 22-24h; IV. After centrifugation and washing with ethanol for 4 to 5 times, the mixture is dried in a vacuum drying oven at 55 to 60° C. to obtain modified nano-silica.

8. The method for preparing a high-adhesive acrylic resin according to claim 7, characterized in that: The preparation method of the modifier is as follows: add a mixed solution of 3 mL of water and 7 mL of ethanol to 0.08 to 0.1 g of γ-methacryloxypropyltrimethoxysilane, and perform ultrasonic dispersion for 10 to 15 minutes to obtain the modifier.

9. The method for preparing a high-adhesive acrylic resin according to claim 1, characterized in that: The preparation method of the modified nanocellulose whisker: 1) Pour 340 mL of 64% sulfuric acid aqueous solution into 18-20 g of absorbent cotton and stir in a water bath at 45-50° C. for 15-20 min; 2) adding 150-180 mL of deionized water, centrifugally washing, and then using acetone and N,N-dimethylformamide to replace the solvent in sequence until the solution concentration reaches 10 wt%; 3) Raise the temperature to 80-85°C, and dropwise add 1.6-2 g of dimethylaminopyridine while stirring, and react for 50-60 min; 4) 0.8-1.3 g of dodecenylsuccinic anhydride is added dropwise, and after the addition is complete, stirring is continued for 3.6-4 h, and then the mixture is cooled to room temperature and washed for 3-5 times to obtain modified nanocellulose whiskers.

Citation Information

Patent Citations

  • Special epoxy acrylic resin composition for LDI photoresist

    CN115926111A